Detection of geological boundaries by 3D gravity inversion for density gradients in different directions - Jing, Lei; Yang, Yabin; Yao, Changli; Qiu, Longjun; Chen, Deyuan; Xu, Menglong (Frontiers in Earth Science, 2022)
The spatial position and dip feature of density boundary are of great significance to the study of fault and tectonic framework. Edge detection methods generally focus on the horizontal position of the boundary, but it is difficult to determine the dip feature clearly. Therefore, a density gradient inversion method is proposed based on the corresponding relationship among gravity forward field, forward kernel matrix and model attributes. Different from conventional gravity inversion, the inversion result of this method is density gradient value. Combined with 3D inversion results of density gradient in different directions, it can directly show the 3D distribution features. Theoretical model shows that the inversion results can not only identify the horizontal position of the boundary, but also qualitatively determine the dip feature of faults. This method has been successfully applied to fault identification in Songliao Basin. According to the joint inversion results, strike feature can be quantitatively identified and dip feature can be qualitatively judged, which makes up for the shortcomings of sparse distribution and poor lateral resolution of existing seismic data.